Interorgan communication in neurogenic heterotopic ossification: the role of brain-derived extracellular vesicles - Weicheng Lu; Jianfei Yan; Chenyu Wang; Wenpin Qin; Xiaoxiao Han; Zixuan Qin; Yu Wei; Haoqing Xu; Jialu Gao; Changhe Gao; Tao Ye; Franklin R. Tay; et al. (Bone Research, 2024)
Abstract Brain-derived extracellular vesicles participate in interorgan communication after traumatic brain injury by transporting pathogens to initiate secondary injury. Inflammasome-related proteins encapsulated in brain-derived extracellular vesicles can cross the blood‒brain barrier to reach distal tissues. These proteins initiate inflammatory dysfunction, such as neurogenic heterotopic ossification. This recurrent condition is highly debilitating to patients because of its relatively unknown pathogenesis and the lack of effective prophylactic intervention strategies. Accordingly, a rat model of neurogenic heterotopic ossification induced by combined traumatic brain injury and achillotenotomy was developed to address these two issues. Histological examination of the injured tendon revealed the coexistence of ectopic calcification and fibroblast pyroptosis. The relationships among brain-derived extracellular vesicles, fibroblast pyroptosis and ectopic calcification were further investigated in vitro and in vivo. Intravenous injection of the pyroptosis inhibitor Ac-YVAD-cmk reversed the development of neurogenic heterotopic ossification in vivo. The present work highlights the role of brain-derived extracellular vesicles in the pathogenesis of neurogenic heterotopic ossification and offers a potential strategy for preventing neurogenic heterotopic ossification after traumatic brain injury. Brain-derived extracellular vesicles (BEVs) are released after traumatic brain injury. These BEVs contain pathogens and participate in interorgan communication to initiate secondary injury in distal tissues. After achillotenotomy, the phagocytosis of BEVs by fibroblasts induces pyroptosis, which is a highly inflammatory form of lytic programmed cell death, in the injured tendon. Fibroblast pyroptosis leads to an increase in calcium and phosphorus concentrations and creates a microenvironment that promotes osteogenesis. Intravenous injection of the pyroptosis inhibitor Ac-YVAD-cmk suppressed fibroblast pyroptosis and effectively prevented the onset of heterotopic ossification after neuronal injury. The use of a pyroptosis inhibitor represents a potential strategy for the treatment of neurogenic heterotopic ossification.